Comparative efficacy, pharmacokinetic, pharmacodynamic activity, and interferon stimulated gene expression of different interferon formulations in HIV/HCV genotype‐1 infected patients. Issue 2 (26th October 2013) - Osinusi, Anu; Bon, Dimitra; Nelson, Amy; Lee, Yu‐Jin; Poonia, Seerat; Shivakumar, Bhavana; Cai, Shu Yi; Wood, Brad; Haagmans, Bart; Lempicki, Richard; Herrmann, Eva; Sneller, Michael; et al.
ABSTRACT The effect of different formulations of interferon on therapeutic response in patients coinfected with HIV and HCV is unclear. In this study, the safety, tolerability, viral kinetics (VK) modeling and host responses among HIV/HCV coinfected patients treated with pegylated‐IFN or albinterferon alfa‐2b (AlbIFN) with weight‐based ribavirin were compared. Three trials treated 57 HIV/HCV coinfected genotype‐1 patients with PegIFN alfa‐2b (1.5 µg/kg/week) (n = 30), PegIFN alfa‐2a (180 µg/week) (n = 10), and AlbIFN (900 µg/q2week) (n = 17) in combination with weight‐based ribavirin (RBV). HCV RNA, safety labs, and interferon stimulated gene expression (ISG) was evaluated. Adverse events were documented at all study visits. HCV viral kinetics using a full pharmacokinetic/pharmacodynamic model was also evaluated. Baseline patient characteristics were similar across the three studies. All three formulations exhibited comparable safety and tolerability profiles and efficacy. VK/PK/PD parameters for all three studies as measured by mean efficiency and rate of infected cell loss were similar between the three groups. Host responses (ISG expression and immune activation markers) were similar among the three groups. All three regimens induced significant ISG at week 4 (P < 0.05) and ISG expression strongly correlated with therapeutic response (r = 0.65; P < 0.01). In summary, a comprehensive analysis of responses to three different interferon formulations in HIV/HCV coinfected patients demonstrated similar effects. Notably, interferon‐based therapy results in a blunted host response followed by modest antiviral effect in HIV/HCV coinfected patients. This suggests that future treatment options that do not rely on host immune responses such as direct antiviral agents would be particularly beneficial in these difficult to treat patients. J. Med. Virol. 86:177–185, 2014. © 2013 Wiley Periodicals, Inc.